2010
DOI: 10.1093/annonc/mdp533
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab combined with chemotherapy for patients with advanced colorectal cancer: a systematic review

Abstract: For patients with advanced colorectal cancer receiving first- or second-line fluoropyrimidine-based chemotherapy, the addition of bevacizumab improves PFS and OS at the expense of increased incidence of toxicity. The magnitude of benefit may differ based on the chemotherapy regimen with which bevacizumab is partnered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
119
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 22 publications
1
119
0
3
Order By: Relevance
“…18 An improvement in survival was found in some studies, and the median survival is 21 months with the addition of biologic agents. [19][20][21] In case of inoperability of liver metastases and in absence of response to systemic chemotherapy, various interventional radiology procedures are considered as an alternative…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…18 An improvement in survival was found in some studies, and the median survival is 21 months with the addition of biologic agents. [19][20][21] In case of inoperability of liver metastases and in absence of response to systemic chemotherapy, various interventional radiology procedures are considered as an alternative…”
mentioning
confidence: 96%
“…[14][15][16][17] A survival benefit has been shown with the addition of bevacizumab to both first-and second-line therapy, and the reported median survival in several studies ranged between 10.2 and 21.5 months. 18 An improvement in survival was found in some studies, and the median survival is 21 months with the addition of biologic agents. [19][20][21] In case of inoperability of liver metastases and in absence of response to systemic chemotherapy, various interventional radiology procedures are considered as an alternative treatment method in the interdisciplinary therapy management.…”
mentioning
confidence: 96%
“…The combination of doublet chemotherapy regimens with biological agents, such as bevacizumab (a humanized monoclonal antibody that inhibits vascular endothelial growth factor (Ferrara et al, 2003) has been shown to prolong PFS, OS and RR although toxicity was also increased (Kabbinavar et al, 2005;Grothey et al, 2008;Hochster et al, 2008;Saltz et al, 2008;Welch et al, 2010;Macedo et al, 2012). Although all of this findings, the optimal combination of first-line treatment is still unclear (Cunningham et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The monoclonal VEGF-A antibody, bevacizumab, has been shown to modestly improve OS in addition to chemotherapy in metastatic CRC in several meta-analyses [105][106][107][108], and is currently established within the standard armamentarium in first line management of this disease. The role for the bevacizumab in EOC is also evolving with two large phase III trials confirming improve PFS in addition to adjuvant chemotherapy following primary debulking surgery [109,110] and in both the recurrent platinum sensitive [111] and resistant settings [112].…”
Section: Targeted Therapeutic Approaches 81 Vegf Inhibitionmentioning
confidence: 99%